A Rare Case of Presacral Paraganglioma Presenting with Hypertensive Encephalopathy - Dhiraj KB.; Mamatha B. (Department of Surgery, UKM Medical Centre, 2015)
Paragangliomas are exceptionally rare tumors in children of neural crest origin. Our case report represents an extremely rare location for paraganglioma including its imaging features, perioperative challenges and histopathological characteristics. In the present case, a 10-year-old boy had headache and blurring of vision for four years but was not diagnosed until he came with malignant hypertension and hypertensive encephalopathy. The symptoms raised urinary catecholamines and CT findings confirmed the diagnosis of a functioning paraganglioma in presacral region. Challenges during surgery are to control the fluctuating blood pressure which may suddenly rise during tumor handling and suddenly fall following its removal. The unusual location of the tumor in pararectal region also made surgical resection difficult. Paragangliomas are rare and should be kept in mind while evaluating a child with hypertension and complete excision is the treatment of choice.